Aurores et crépuscules dans la Thébaïde de Stace - Tomcik, Melissande (Brill, 2023)
The open access publication of this book has been published with the support of the Swiss National Science Foundation. Ce livre propose une étude intertextuelle des descriptions d'aurores et de crépuscules dans la Thébaïde de Stace. Les images poétiques de l'Aurore aux doigts de rose ou du char solaire plongeant dans l'Océan cachent un travail minutieux sur la tradition littéraire antérieure. Les remarquables aurores et crépuscules de la Thébaïde illustrent parfaitement la façon dont les caractéristiques traditionnelles du motif peuvent être détournées pour transmettre un nouveau message. Chaque chapitre de cet ouvrage examine en détail un des aspects lié aux aurores et aux crépuscules : expressions formulaires, rôle structurant, fonction lumineuse et temporelle, potentiel métaphorique. This book offers an intertextual study of dawn and dusk descriptions in Statius' Thebaid. Poetic images such as rosy-fingered Dawn and the fiery chariot of the Sun sinking into the Ocean are the result of learned work on the previous literary tradition. The striking dawn and dusk descriptions in the Thebaid offer a perfect illustration of the way in which the traditional characteristics of the motif can be remodelled to produce new meaning. Each chapter in this monograph examines one of the aspects associated with dawns and dusks: formulaic diction, structuring role, relation to time and light, allegory.